Best Answer

x + y = 4 and y = 2x + 1

The first equation can be rearranged to show x = 4 - y (Effectively y has been subtracted from both sides)

Now substitute for 'x' in the equation y = 2x +1

y = 2(4 - y) + 1 = 8 - 2y + 1 = 9 - 2y

y = 9 - 2y can be rearranged to show 3y = 9 (Effectively adding 2y to both sides)

and by dividing by 3 then y = 3.

Now substitute the value for y in x + y = 4

x + 3 = 4 ; x = 1

Answer : x = 1, y = 3

Q: How do you solve x plus y equals 4 and y equals 2x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 1 = 9 2x = 9 - 1 2x = 8 2x/2 = 8/2 x=4

X = 0 (zero) Y = -1 (neg 1)

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

It can be anything. Example: x=1

If we assume that it equals zero and you wish to solve for x, then the answer is:-x2 + 2x - 3 = 0x2 - 2x + 3 = 0x2 -2x + 1 = -2(x - 1)2 = -2x - 1 = ± √(-2)x = 1 ± i√2

Related questions

2x+32 = 1 2x = 1-32 2x = -31 x = -15.5

2x+1 = 9 2x = 9-1 2x = 8 x = 4

If: x+1+2x = 1x+5 Then: x = 2

2x + 1 = 9 2x = 9 - 1 2x = 8 2x/2 = 8/2 x=4

X = 0 (zero) Y = -1 (neg 1)

2x + 7 = 1 Therefore, 2x = -6 x = -6/2 x = -3

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

It can be anything. Example: x=1

If we assume that it equals zero and you wish to solve for x, then the answer is:-x2 + 2x - 3 = 0x2 - 2x + 3 = 0x2 -2x + 1 = -2(x - 1)2 = -2x - 1 = ± √(-2)x = 1 ± i√2

2x + 5x - 1 = 9x 7x - 1 = 9x -1 = 9x - 7x -1 = 2x -1/2=x

2x+8 = 6 2x = 6-8 2x = -2 x = -1

2x + 2/3= 5/3 2x= 3/3 2x=1 x=1/2